2009
DOI: 10.1902/jop.2009.090030
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Full‐Mouth and Partial‐Mouth Scaling and Root Planing in Treating Chronic Periodontitis in Subjects With Type 2 Diabetes

Abstract: FMSRP and PMSRP were equally effective in treating chronic periodontitis in subjects with type 2 diabetes, without significant improvements in the glycemic control at 3 and 6 months. Considering the periodontal therapy as a whole (FMSRP plus PMSRP), subjects with better-controlled diabetes exhibited a benefit in CAL at 6 months compared to subjects with poorly controlled disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
75
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 44 publications
11
75
1
3
Order By: Relevance
“…These findings suggest that the mechanical periodontal treatment performed within two consecutive days or in weekly appointments produced comparable microbiological benefits up to 12 months in the diabetic subjects, supporting our previous clinical and immunological results. 13,14 The current study demonstrated that FMSRP and PMSRP significantly reduced the individual levels and the proportions of three well-recognized periodontal pathogens (T. forsythia, P. gingivalis and T. denticola) in type 2 diabetic subjects. In addition, both therapies also increased the proportion of the host-compatible Actinomyces species.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…These findings suggest that the mechanical periodontal treatment performed within two consecutive days or in weekly appointments produced comparable microbiological benefits up to 12 months in the diabetic subjects, supporting our previous clinical and immunological results. 13,14 The current study demonstrated that FMSRP and PMSRP significantly reduced the individual levels and the proportions of three well-recognized periodontal pathogens (T. forsythia, P. gingivalis and T. denticola) in type 2 diabetic subjects. In addition, both therapies also increased the proportion of the host-compatible Actinomyces species.…”
Section: Discussionsupporting
confidence: 49%
“…4 On the other hand, due to the restricted number of appointments required for FMSRP, one could argue that this approach would promote a poorer outcome, due to the risk of leaving greater amounts of residual calculus and/or the reduction in the number of sessions of plaque control reinforcement. However, the findings from the current and several previous studies [5][6][7][8][9][10][11][12][13][14] have provided considerable evidence that the FMSRP approach does not result in a worse or better clinical or microbiological outcome than the PMSRP approach. Therefore, as FMSRP and PMSRP produce similar beneficial clinical and microbiological results and are well tolerated by patients, both modalities seem to be equally adequate for the initial nonsurgical periodontal treatment in diabetics and non-diabetics and should be used according to patient's needs and preferences and operator abilities.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Non-surgical periodontal therapy is able to reduce the amount of viable periodontopathogens by restoring the local microbiota compatible with periodontal health in diabetic and non-diabetic patients [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%